Laser Composite Surfacing of Ni-WC Coating on AA5083 for Enhancing Tribomechanical Properties - Quazi, M.M.; Fazal, M.A.; Haseeb, A.S. Md. Abdul; Yusof, F.; Masjuki, Haji Hassan; Arslan, A. (Taylor & Francis, 2017)
Laser composite surfacing (LCS) has emerged as an alternative photon-driven manufacturing technology for the fabrication of composite coatings to enhance the tribomechanical properties of various aluminum alloys. The current research presents an analysis on optimization of laser processing parameters for Ni-WC composite coating deposited on AA5083 aluminum alloy in order to improve its tribomechanical properties. To carry out the investigation, Taguchi's optimization method using a standard L16 (34) orthogonal array was employed. Thereafter, the results were analyzed using signal-to-noise (S/N) ratio response analysis and Pareto analysis of variance (ANOVA). Finally, confirmation tests with the best parameter combinations obtained in the optimization process were made to demonstrate the progress made. Results showed that the surface hardness (953 Hv) and roughness (0.81 μm) of coated AA5083 samples was enhanced by 9.27 and 13.14%, respectively. The tribological behavior of LCS samples was investigated using a ball-on-plate tribometer against a counterbody of 440c steel. It was revealed that the wear of the Ni-WC-coated samples improved by around 2.5 times. For lower applied loads, the coating exhibited an abrasive wear mode and a reduction in plastic deformation.